CHEWING XYLITOL CANDY AND PROBIOTIC CANDY ON THE GROWTH OF DENTAL PLAQUE AND NUMBER OF COLONY OF STERPTOCOCCUS MUTANT BACTERIA - Rahmawati Sri Praptiningsih; Rozaan Wakhid Amien; Rosa Pratiwi (ODONTO : Dental Journal, 2022)
Background: Caries or cavities is a disease in the hard tissue of the teeth characterized by damage to enamel and dentin caused by the metabolic activity of bacteria in plaque which can cause demineralization due to the products of microorganisms. Xylitol gum and probiotics can be used to reduce the plaque index and the number of Streptococcus mutans colonies. The purpose of this study was to compare the effect of chewing gum containing xylitol and probiotics on plaque growth and to determine the number of Streptococcus mutans colonies in students of the Faculty of Dentistry, Sultan Agung Islamic University.Method: This study used an experimental research method with a randomized posttest only control group design used 30 respondents divided into 3 groups, namely the xylitol, probiotics, and sugar groups. Each group had a good oral hygiene index (OHIS) and then checked the plaque index and the number of Streptococcus mutans colonies before and after chewing gum for 1 minute. Data were analyzed in the Laboratory of Microbiology, Faculty of Medicine, Sultan Agung Islamic University. Data were analyzed using paired t-test and Wilcoxon test. Result: The p value <0.05 or there was no significant decrease in each group. Conclusion: There is an effect of chewing gum containing xylitol and probiotics on the number of Streptococcus mutans and plaque index, but there is no significant difference between the plaque index and the number of Streptococcus mutans colonies.